Investigation of tensile deformation behavior of a TWIP/TRIP metastable β titanium alloy at typical temperature part Ⅰ: Room temperature - Y.B. Zhang; S.W. Xin; G.J. Zhang; T. Li (Materials & Design)
The tensile behavior and deformation mechanism of Ti-10Mo alloy at room temperature (298 K) were investigated. The results show that the alloy has an ultimate tensile strength (UTS) of 744 MPa and a high yield strength (YS) of 662 MPa, as well as an excellent elongation (El) after fracture of 38 %, outperforming Ti-15Mo alloy under the same conditions. The superior strength and plasticity of Ti-10Mo alloy at 298 K are attributed to the activation of both {332}〈113> twinning and SIM α“ during deformation. The sequence of different deformation mechanisms is as follows: in the initial stage of deformation, dislocation slip can be extensively activated and continues to occur during subsequent deformation; in the middle stage of deformation, primary and secondary {332}〈113〉 twinning and SIM α” are activated simultaneously, resulting in a continuous increase in work hardening rate; in the later stage of deformation, the alloy can further deform through {1 1 1}α“ twinning. The higher YS may be due to the optimal quantity and size of athermal ω phase in Ti-10Mo alloy, which increases the YS without significantly affecting plasticity. Meanwhile, Quenching vacancies can also increase the YS of the alloy. The three stages of the work hardening rate curve correspond to the activation of the dislocation slip mechanism, the activation of the {332}〈113〉 twinning and SIM α” and the stop of the {332}〈113〉 twinning and SIM α“.